Greenhouse Farming in Kitengela, Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
A number of farmers in arid and semi arid lands in Kenya are undertaking intensive crop production in greenhouses. Shown here are pictures taken from Kitengela, a semi arid area in Kenya. The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) East Africa program is undertaking research to help farmers build resilience to climate change. Photos: V. Atakos and S. Kilungu( CCAFS)